2013
DOI: 10.1073/pnas.1309991110
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 2 regulates selective autophagic α-synuclein clearance and suppresses its toxicity in vivo

Abstract: An increase in α-synuclein levels due to gene duplications/triplications or impaired degradation is sufficient to trigger its aggregation and cause familial Parkinson disease (PD). Therefore, lowering α-synuclein levels represents a viable therapeutic strategy for the treatment of PD and related synucleinopathies. Here, we report that Polo-like kinase 2 (PLK2), an enzyme up-regulated in synucleinopathy-diseased brains, interacts with, phosphorylates and enhances α-synuclein autophagic degradation in a kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
203
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(221 citation statements)
references
References 60 publications
13
203
1
4
Order By: Relevance
“…However, the relevance of αS phosphorylation at S129 for neurotoxicity and disease remains controversial (Basso et al, 2013). While some reports report a beneficial effect (Kuwahara et al, 2012;Oueslati et al, 2013), others identified deleterious consequences (Chen and Feany, 2005;Sato et al, 2011). A separate study found no effects of this posttranslational modification (McFarland et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevance of αS phosphorylation at S129 for neurotoxicity and disease remains controversial (Basso et al, 2013). While some reports report a beneficial effect (Kuwahara et al, 2012;Oueslati et al, 2013), others identified deleterious consequences (Chen and Feany, 2005;Sato et al, 2011). A separate study found no effects of this posttranslational modification (McFarland et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Because the phosphorylation of S129 appeared to have no consistent effect on α-syn function in the cell, it has been unclear whether the process does anything more than reflect the magnitude of total α-syn levels in diseased neurons. In their article in PNAS, Oueslati et al (6) now reveal a unique and unexpected effect coupled to S129 phosphorylation.…”
mentioning
confidence: 94%
“…Although this may at first appear irrelevant to α-syn, which is mostly located at presynaptic terminals in neurons, it should be noted that increased synaptic activity promotes α-syn secretion from neurons, and that phosphorylated α-syn is enriched in the secreted fraction of some cell types (15,16). Given the suggestion that α-syn secretion is a key step in a prion-like cell-to-cell transfer of α-syn pathology and thereby contributes to progression of PD symptoms (17), the findings by Oueslati et al (6) suggest that PLK2 might influence transmission of misfolded α-syn variants.…”
mentioning
confidence: 99%
See 2 more Smart Citations